Survival inequity in vulnerable populations with early-stage hepatocellular carcinoma: a United States safety-net collaborative analysis. Issue 6 (June 2021) - Kronenfeld, Joshua P.; Ryon, Emily L.; Goldberg, David; Lee, Rachel M.; Yopp, Adam; Wang, Annie; Lee, Ann Y.; Luu, Sommer; Hsu, Cary; Silberfein, Eric; Russell, Maria C.; Merchant, Nipun B.; et al.
Abstract: Background: Access to health insurance and curative interventions [surgery/liver-directed-therapy (LDT)] affects survival for early-stage hepatocellular carcinoma (HCC). The aim of this multi-institutional study of high-volume safety-net hospitals (SNHs) and their tertiary-academic-centers (AC) was to identify the impact of type/lack of insurance on survival disparities across hospitals, particularly SNHs whose mission is to minimize insurance related access-to-care barriers for vulnerable populations. Methods: Early-stage HCC patients (2012–2014) from the US Safety-Net Collaborative were propensity-score matched by treatment at SNH/AC. Overall survival (OS) was the primary outcome. Multivariable Cox proportional-hazard analysis was performed accounting for sociodemographic/clinical parameters. Results: Among 925 patients, those with no insurance (NI) had decreased curative surgery, compared to those with government insurance (GI) and private insurance [PI, (PI-SNH:60.5% vs. GI-SNH:33.1% vs. NI-SNH:13.6%, p < 0.001)], and decreased median OS (PI-SNH:32.1 vs. GI-SNH:22.8 vs. NI-SNH:9.4 months, p = 0.002). On multivariable regression controlling for sociodemographic/clinical parameters, NI-SNH (HR:2.5, 95% CI:1.3–4.9, p = 0.007) was the only insurance type/hospital system combination with significantly worse OS. Conclusion: NI-SNH patients received less curative treatment than other insurance/hospitals types suggesting that treatment barriers, beyond access-to-care, need to be identified and addressed to achieve survival equity in early-stage HCC for vulnerable populations (NI-SNH).